Association of Posttraumatic Stress Disorder and Depression With All-Cause and Cardiovascular Disease Mortality and Hospitalization Among Hurricane Katrina Survivors With End-Stage Renal Disease - Edmondson, Donald (American Public Health Association, 2013)
Objectives. We determined the association of psychiatric symptoms in the year after Hurricane Katrina with subsequent hospitalization and mortality in end-stage renal disease (ESRD) patients. Methods. A prospective cohort of ESRD patients (n = 391) treated at 9 hemodialysis centers in the New Orleans, Louisiana, area in the weeks before Hurricane Katrina were assessed for posttraumatic stress disorder (PTSD) and depression symptoms via telephone interview 9 to 15 months later. Two combined outcomes through August 2009 (maximum 3.5-year follow-up) were analyzed: (1) all-cause and (2) cardiovascular-related hospitalization and mortality. Results. Twenty-four percent of participants screened positive for PTSD and 46% for depression; 158 participants died (79 cardiovascular deaths), and 280 participants were hospitalized (167 for cardiovascular-related causes). Positive depression screening was associated with 33% higher risk of all-cause (hazard ratio [HR] = 1.33; 95% confidence interval [CI] = 1.06, 1.66) and cardiovascular-related hospitalization and mortality (HR = 1.33; 95% CI = 1.01, 1.76). PTSD was not significantly associated with either outcome. Conclusions. Depression in the year after Hurricane Katrina was associated with increased risk of hospitalization and mortality in ESRD patients, underscoring the long-term consequences of natural disasters for vulnerable populations.